The impact of internal, external, and competitor factors on marketing strategy performance. (2nd October 2020) - Ibrahim, Essam B.; Harrison, Tina
ABSTRACT: Strategy formulation is commonly understood as the match between a firm's internal resources and skills and its external environment. Marketing strategy performance is the function of a dynamic, interactive process incorporating internal firm resources, external environmental factors, and competitive actions. The study aims to assess the impact of competitor actions on marketing strategy performance. We develop a model that accommodates the effects of 29 variables (comprising internal marketing strategy variables, external environmental factors and competitors' marketing mix variables) on business performance. We empirically test the model using simultaneous equation modelling of time-series data on UK car manufacturers collected from publically available resources and annual reports. The results show that external factors, in particular competitors' marketing mix elements, have a greater influence on a company's business performance than internal (marketing and non-marketing) strategy variables. Implications for marketing theory and management are discussed.